The influence of hardware impairment on the system performance of two-way relaying network - Le Anh Vu; Minh Tran; Van-Duc Phan; Hoang-Nam Nguyen; Thanh-Long Nguyen (International Journal of Electrical and Computer Engineering (IJECE), 2019)
In this research, the system performance of the half-duplex two-way relay network under hardware impairment condition is presented and investigated. In this system model, the time switching protocol and amplify-and-forward (AF)-based are considered. First, of all, the analytical expressions of the outage probability, and achievable throughput with the exact closed form and asymptotic form were proposed and derived. Furthermore, the research results are derived and convinced by Monte-Carlo calculation. The numerical results demonstrated and convinced the analytical and the simulation results are agreed for all possible system parameters.